2015
DOI: 10.1007/s11739-015-1205-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ACEI-related angioedema with icatibant: a case series

Abstract: No specific drugs are licensed for the treatment of ACE inhibitor (ACEI)-acquired angioedema (ACEI-AAE). Icatibant, an antagonist of the B2 receptor of bradykinin, is a potential treatment for this condition; however, its use in this setting is poorly documented. We report here clinical outcomes of 13 patients with ACEI-AAE treated with icatibant, in a real-life setting. Thirteen patients on ACEI seen in an Emergency Department (ED) with angioedema involving face, lips or the upper airways were analyzed. Angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 22 publications
0
22
0
5
Order By: Relevance
“…38 Two case series comparing icatibant-treated patients with those previously treated with standard therapies found statistically significant improvements in time to complete symptom resolution. 46,47 A phase II randomized placebo-controlled trial of 27 patients with ACEI-IA presenting within 10 hours of symptom onset showed a statistically significant shorter time to complete edema resolution compared with standard therapy. 49 In clinical trials for HAE, almost all patients receiving icatibant experienced a self-limiting injection site reaction (97%), including erythema, edema, pain, and pruritus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Two case series comparing icatibant-treated patients with those previously treated with standard therapies found statistically significant improvements in time to complete symptom resolution. 46,47 A phase II randomized placebo-controlled trial of 27 patients with ACEI-IA presenting within 10 hours of symptom onset showed a statistically significant shorter time to complete edema resolution compared with standard therapy. 49 In clinical trials for HAE, almost all patients receiving icatibant experienced a self-limiting injection site reaction (97%), including erythema, edema, pain, and pruritus.…”
Section: Discussionmentioning
confidence: 99%
“…46 Two other case series noted no adverse events after icatibant administration. 47,48 Adverse events of redness, swelling, pain and itching and sensation of warmth were reported in patients receiving icatibant in the clinical trial; however, none were deemed serious. 49 There are no published studies on cost-effectiveness of the off-label use of agents approved for HAE in the management of ACEI-IA to justify their place in therapy and inclusion in ED inventory.…”
Section: Discussionmentioning
confidence: 99%
“…It is administered subcutaneously (30-mg/3-ml syringes). Its effectiveness has been shown in multiple clinical trials for patients with types I and II HAE [47,48] and in case series in AAE-ACEi [49]. No serious adverse reactions have been reported.…”
Section: Bradykinin Receptor Antagonistmentioning
confidence: 95%
“…[64][65][66] The severity of ACEi-A varies; mild ACEi-A is more frequent, but symptoms can recur and potentially worsen overtime. 70 Rather, fresh frozen plasma, C1 esterase inhibitor or tranexamic acid had been found to be effective in several case series and are often utilized in real-life practice when first-line treatment fails. 23,30,69 A factor which often obscures or delays correct diagnosis is the variable time to onset.…”
Section: Clinical Featuresmentioning
confidence: 99%